Long-term outcomes of congenital adrenal hyperplasia due to 21-hydroxylase deficiency: a retrospective study from a tertiary care center in Saudi Arabia - Aldalaan, Haneen; Alsagheir, Afaf; Alghamdi, Nujud; Alhuthil, Raghad; Almslam, Maha; Al-Hamed, Mohamed H. (Frontiers in Endocrinology, 2025)
IntroductionData on congenital adrenal hyperplasia (CAH) disorders in the Saudi population are limited. This retrospective study assessed the clinical characteristics ofadolescents and adults with 21-hydroxylase CAH alongside the long-term outcomes of chronic glucocorticoid replacement therapy. MethodsThe study was conducted at the King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia. The subjects included patients (aged ≥ 14 years) with 21-hydroxylase CAH, who attended the endocrine clinic between 2019 and 2021.ResultsThe study found that among the 108 patients with 21-hydroxylase deficiency considered, predominantly females (66.67%), with a median age of 21 years (IQR: 18–30), 93.51% had the classic salt-wasting form, while 6.49% had the nonsalt-wasting form. Glucocorticoid therapy for the patients included prednisone (46.3%), hydrocortisone (37.97%), and dexamethasone (12.03%). Short stature was observed in 30% of the patients, while obesity affected 35.19%. Among the females, 58.33% had oligomenorrhea. In addition, testicular adrenal rest tumors (TARTs) were detected in 44.44% of the males. Metabolic issues included high cholesterol in 95.65%, with 17.33% exhibiting prediabetics. Genetic testing identified CYP21A2 mutations in all patients tested.Discussionshort stature, obesity, and menstrual irregularities are highly prevalent in females, whereas TARTs are common in males. Although metabolic and bone health outcomes are generally favorable, the variability in hormonal control and its associated complications underscores the need for individualized glucocorticoid therapy. Continuous monitoring and improved treatment strategies are essential for optimizing the quality of life of patients with CAH.